Intelligent response bilayer hydrogel with controllable deformation-recovery and shape memory. (5th May 2021) - Chen, Yang; Liu, Tao; Wang, Guoyin; Liu, Jianzhi; Zhao, Ling; Zhang, Ripeng; Yu, Yueqin
Graphical abstract: Highlights: Combine controllable deformation with shape memory properties. Control of the deformation recovery process. Excellent anti-fatigue ability. Feasibility as an intelligent water temperature alarm switch. Abstract: Although bilayer hydrogel (BLGEL) has received increasing interest owing to their promising applications in artificial muscles, soft robotics, and flexible electronics, it is still a challenging task to realize controllable deformation-recovery and shape memory in one hydrogel. Herein, a novel type of freeze-thaw bilayer hydrogel (F-BLGEL) was successfully fabricated, including a top layer of the semi-interpenetrating network of polyacrylamide-chitosan (PAM-CS) and a bottom layer of the copolymerization network of P (N-isopropylacrylamide-2-acrylamido-2-methylpropanesulfonic acid) (P(NIPAm-AMPS)). Not limited with the unidirectional temporary deformation occurs in 30 s, the hydrogel is also achieved permanent deformation in the opposite direction, and the deformation recovery process can be accurately controlled by calculating the deformation recovery rate, so that the F-BLGEL hydrogel exhibits the outstanding controllable deformation-recovery performance. The shape fixation ratio Rf and shape recovery ratio Rr reached 200% and 100%, respectively, the hydrogel has excellent fatigue resistance in the five-cycle test, which reflects excellent shape memory ability. Overall, based on the intelligent responsive, the F-BLGEL hydrogel was designed as a temperature-controlled device, which can be treated as a candidate material for intelligent controlled device.